Searching for Economic Balance in Business Method Patents - Keith E. Maskus; Eina Vivian Wong (Washington University Journal of Law & Policy, 2002)
Business method patents (BMPs) award exclusive rights to inventors for novel techniques that perform commercial functions not embodied in specific physical inventions. Perhaps because of the novel and intangible nature of business methods, BMPs commanded little attention from economists, even though legal scholars have covered selected economic issues implicated by BMPs in qualitative terms. In this Essay, we hope to shed some light on the issue by considering economic arguments for awarding patents for business concepts. Many of these arguments focus on the wisdom of broad and exclusive rights in sectors that are critical for economic growth, where innovation is dynamic and incremental, and where standards and network effects are significant. In our view, economic analysis cannot support the BMP system as it currently operates. This conclusion is buttressed by the limited empirical evidence available for BMPs. In brief, the patent system is imbalanced in favor of inventors to the detriment of the public good. Thus, Congress and the USPTO should significantly modify the standards and procedures for granting and enforcing business method patents.
Keywords: Business; Patents; Business method patents; Economics; United States